To solve this expression, we will simplify each part separately and then divide the results.
First, we simplify (8/9) x (-3/4).
To multiply fractions, we multiply the numerators together and the denominators together.
(8/9) x (-3/4) = (8 x -3) / (9 x 4) = -24/36
The fraction -24/36 can be simplified by dividing the numerator and denominator by their greatest common divisor, which is 12.
-24/36 = (-24 ÷ 12) / (36 ÷ 12) = -2/3
Now, we simplify (1/9) x (-4/5).
(1/9) x (-4/5) = (1 x -4) / (9 x 5) = -4/45
Finally, we divide (-2/3) by (-4/45).
To divide fractions, we multiply the first fraction by the reciprocal of the second fraction.
(-2/3) ÷ (-4/45) = (-2/3) x (45/-4)
We can simplify before multiplying by dividing the numerator and denominator by their greatest common divisor, which is 1.
(-2/3) x (45/-4) = (-2 x 45) / (3 x -4) = -90/-12
Again, we simplify by dividing the numerator and denominator by their greatest common divisor, which is 6.
-90/-12 = (-90 ÷ 6) / (-12 ÷ 6) = 15/2
So, (8/9) x (-3/4) ÷ (1/9) x (-4/5) ÷ (3/5) simplifies to 15/2.
Use the properties of operations and rules for multiplying and dividing to solve: (8/9) x (-3/4) divide (1/9) x (-4/5) divide (3/5)
1 answer